Integration of the 4Cs in a CLIL-based textbook for geology students: A case study - Đorđević, Marija (Technium Social Sciences Journal, 2023)
Even though the CLIL method of foreign language teaching has been present for more than thirty years, the lack of adequate CLIL-specific teaching material on the market remains an undiminished challenge. One of the reasons may be the scrutiny under which the authors, language teachers, of a CLIL textbook would find themselves, since they would have to grapple with both the linguistic and non-linguistic matter equally. The textbooks “English language for geology students 1 and 2” are an attempt to fully cover a specific subject matter, in this case geology, all the while focusing on fostering student autonomy and intercultural competence. The textbooks follow the principles of the CLIL method in a novel and innovative way, putting special focus on the last of the 4Cs: culture, through geomythology and comic strips. The paper is divided into four parts: introduction, a discussion on CLIL teaching materials, structure and content of the chosen textbooks and concluding remarks. The author will attempt to provide an overview of the textbooks within the CLIL context and to show how they manage to cover the criteria set by CLIL in assuring a stress-free learning environment in which students can acquire skills necessary for success outside the walls of a university classroom.